2018
DOI: 10.1080/00036846.2018.1527444
|View full text |Cite
|
Sign up to set email alerts
|

Citizens’ support for inter-municipal cooperation: evidence from a survey in the German state of Hesse

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 37 publications
4
28
0
Order By: Relevance
“…For the case of inter-municipal cooperation the German state of Hesse,Bergholz and Bischoff (2019) analyze survey data that indicate that support for cooperation is weaker for respondents that have high trust in their local government, a finding that supports our expectation.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…For the case of inter-municipal cooperation the German state of Hesse,Bergholz and Bischoff (2019) analyze survey data that indicate that support for cooperation is weaker for respondents that have high trust in their local government, a finding that supports our expectation.…”
supporting
confidence: 62%
“…Brink (2004) andLapointe (2018) find that preference heterogeneity matters for popular decisions on splits, too Lapointe (2018). finds that voters are willing to pay additional taxes to live in their jurisdiction of choice.4 In a related study,Bergholz & Bischoff (2019) recently study the determinants on attitudes towards intermunicipal cooperation using a survey of local citizens in the German state of Hesse.…”
mentioning
confidence: 99%
“…Higher education per se also gives citizens better capacity to learn about a merger and therefore to better assess its potential benefits and negatives. Bergholz andBischoff (2019, 1275) indeed found that both income and education affected being supportive of municipal co-operation.…”
Section: Demographic Socio-economic and Social Factorsmentioning
confidence: 99%
“…In smaller communities and municipalities the distance between voters and politicians is smaller and social ties can often be shortcuts into influencing politics. Thus, a proposed merger into a larger jurisdiction would increase the distance between the voters and representatives, both physically and socially (Bergholz & Bischoff 2019). This might induce concerns among citizens about their ability to have a say about matters in the merged larger municipality and might therefore lead to more negative opinions on a proposed municipal merger.…”
Section: Political Efficacy and Political Trustmentioning
confidence: 99%
“…Accordingly, IMC increases their frequency interaction with people outside their peer group and thus causes utility losses among citizens who prefer to interact with their peers only (e.g., Brasington, 2003;Alesina et al, 2004). Thus, citizens are more reluctant to support IMC in these fields (e.g., Norris, 2001;Bergholz and Bischoff, 2016).…”
Section: Data and Institutional Backgroundmentioning
confidence: 99%